Dietary patterns and risk of nonfatal acute myocardial infarction in Costa Rican adults - Martínez Ortiz, José Antonio (2006)
Cardiovascular disease (CVD) has become an important public health problem in transition countries in Latin America (Medina and Kaempffer, 2000; Cubillos-Garzón et al., 2004; Ventura and Mehra, 2004; World HealthOrganization, 2004). Because changes in dietary intake are, in part, likely responsible for the increase in CVD during the past 20–30 years (Popkin, 2001), it is essential to identify foods that could play a role on CVD in developing countries. Food pattern analysis has become a valuable tool to examine the effects of diet on chronic disease (Jacques and Tucker, 2001; Hu, 2002). A major advantage of this procedure is that it takes into account multiple dietary factors, including nutrient and non-nutrient components, which could have complex effects on disease risk (Hu, 2002). In the context of Western countries, two main patterns that relate to CVD have been identified. In one study in men (Hu, 2002), a Western dietary pattern consisting primarily of red and processed meat, refined grains, sweets and desserts, French fries, and high-fat dairy products was associated with increased risk of coronary heart disease. In Denmark, a prudent dietary pattern consisting of whole meal bread, fruit, and vegetables was protective against all cause and cardiovascular mortality (Osler et al ., 2001). In the same study, no association with mortality was found for a Western pattern characterized by high intake of meat products, potatoes, white bread, butter, and lard. Consistently, a Mediterranean style diet which includes olive oil, fiber, fruits, vegetables, fish and alcohol, and reduced in meat and meat products was also protective against myocardial infarction (MI) (Martinez-Gonzalez et al ., 2002). The purpose of our study is to identify dietary patterns that are associated with risk of incident MI in Costa Rica, a Latin American country in transition (Reddy, 2004).